Cannabidiol enhances microglial phagocytosis via transient receptor potential (TRP) channel activation. (May 2014) - Hassan, Samia; Eldeeb, Khalil; Millns, Paul J; Bennett, Andrew J; Alexander, Stephen P H; Kendall, David A
<x xml:space="preserve">Abstract</x> Background and Purpose Microglial cells are important mediators of the immune response in the CNS. The phytocannabinoid, cannabidiol (CBD), has been shown to have central anti‐inflammatory properties, and the purpose of the present study was to investigate the effects of CBD and other phytocannabinoids on microglial phagocytosis. Experimental Approach Phagocytosis was assessed by measuring ingestion of fluorescently labelled latex beads by cultured microglial cells. Drug effects were probed using single‐cell Ca2+ imaging and expression of mediator proteins by immunoblotting and immunocytochemistry. Key Results CBD (10 μM) enhanced bead phagocytosis to 175 ± 7% control. Other phytocannabinoids, synthetic and endogenous cannabinoids were without effect. The enhancement was dependent upon Ca2+ influx and was abolished in the presence of EGTA, the Ca2+ channel inhibitor SKF96365, the transient receptor potential (TRP) channel blocker ruthenium red, and the TRPV1 antagonists capsazepine and AMG9810. CBD produced a sustained increase in intracellular Ca2+ concentration in BV‐2 microglia and this was abolished by ruthenium red. CBD rapidly increased the expression of TRPV2 and TRPV1 proteins and caused a translocation of TRPV2 to the cell membrane. Wortmannin blocked CBD enhancement of BV‐2 cell phagocytosis, suggesting that it is mediated by PI3K signalling downstream of the Ca2+ influx. Conclusions and Implications The TRPV‐dependent phagocytosis‐enhancing effect of CBD suggests that pharmacological modification of TRPV channel activity could be a rational approach to treating neuroinflammatory disorders involving changes in microglial function and that CBD is a potential starting point for future development of novel therapeutics acting on the TRPV receptor family.